Proposed exit profile consistent with Civic Education needs based on an analysis of the curriculum design of the Social Studies and Civic Education Program of the School of History, Universidad Nacional de Costa Rica. - Durán Valverde, Wendy (2014)
This article the curriculum development of the career analyzes Enseñanza de los Estudios Sociales y Educación Cívica, Universidad Nacional of Costa Rica, with the aim that it answers to formulating a profile of identical exit to the needs of the education of the Civic Education, in order to re-design the current profile of exit of the Baccalaureate in the above mentioned career, in order that partner agrees with the context - educationally in that there are unrolled the teachers of civic education.